(untitled) (International Journal of Engineering and Computer Science, 2016)
v This is about relay based CRN and beamforming spectrum sharing CRN. In relay based CRN the cognitive nodes which are far away from primary user (PU) may not be able to detect the PU due to severe fading in channel. To improve the efficiency of spectrum sensing we propose a cooperative communication scheme based on cognitive relaying. In beamforming spectrum sharing two conflicting challenges are how to maintain the interferences generated by the CRN to the primary n/w below an acceptable threshold level while maximizing the sum-rates of the cognitive radio network. We present two beamforming methods, modified zero forcing beamforming and transmit receive beamforming .the zero forcing beamforming is modified by adding the channel gain between the cognitive radio base station and the primary user to meet the two conflicting goals, the orthogonality of transmit beam in MIMO beamforming by Gram-schmidt method achieves the first goal that the primary user is interference free to satisfy the second goal, self interference is reduced by the constrained minimization of the mean output array of cognitive receivers. To reduce complexity of the system, the number of cognitive radio users must be limited. Keywords: MIMO, Beamforming, Cognitive radio, Cooperative communication